A DEMATEL-based approach of multi-criteria evaluation for urban fire and emergency facilities - Nyimbili, Penjani Hopkins; Erden, Turan; Mwanaumo, Erastus Misheng'u (Frontiers in Environmental Economics, 2023)
With the increasing complexity of rapidly growing urban environments and interaction of humans, socio-economic and political systems, the global urgency of applying sustainable risk management planning strategies, comprehensively for urban fire risk reduction activities becomes increasingly evident in most fire-prone megacities worldwide such as Istanbul.The current research aims to examine the complex interrelationships and levels of influence among the criteria previously determined for optimally selecting new urban infrastructure for fire and emergency services in Istanbul as part of the fire risk mitigation planning efforts applying the MCDM method of Decision-Making Trial and Evaluation Laboratory (DEMATEL). Useful insights were generated from the study by constructing an intelligible structural model visually in form of a digraph involving analysis of causal relationships among criteria and their directional influences as well as corresponding degrees of strength. The findings reveal that the high population density (HPD) is the most critical criterion followed by the density of hazardous materials (DHM) criterion in effectively planning new urban facilities for fire and emergency services and thus significantly influence and impact all the other criteria, while the distance to earthquake risk (DER) criterion does not influence any other criteria and consequently not essential in the planning procedure. The DEMATEL model results were validated in terms of levels of criteria significance using previous studies and shown to be in high correlation.In this regard, these contextual relationships established would contribute towards an integrated fire risk mitigation planning policy formulation in urban environments through the engagement of all decision-makers across various backgrounds and disciplines such as urban and city planners, engineers, emergency and risk managers and administrators, socio-economic and environmental experts, fire service industry practitioners and local community leaders.